BAHASA JARGON PADA KOMUNITAS REMAJA DI SITUBONDO (ANALISIS DISKRIPSI KUALITATIF PENGGUNAAN BAHASA JARGON PADA KOMUNITAS REMAJA DI SITUBONDO) - Aenor Rofek (Relawan Jurnal Indonesia, 2018)
Jargon in a community aims to create an exclusive language or languages understood by the group and as a manifestation of the existence of a group. It is interesting to study jargon in a certain community. Jargon contained in the teen community is very varied. Jargon used in the teen community in Situbondo is varied in their form and characteristics. A form of jargon includes (1) the form of the lexicon consists of a basic word, affix, abbreviations and acronyms; The characteristics of jargon include (1) jargon is internal, (2) jargon serves to identify themselves, (3) jargon such as shortening of the word. This study was conducted to reveal the forms and characteristics of jargon in teen community in Situbondo